1997
DOI: 10.1037/1076-8998.2.4.312
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the use and perceptions of employee assistance programs at six worksites.

Abstract: Employee assistance programs (EAPs) have gained significant importance in contemporary worksites. This article uses data from 6 case studies to examine several research questions regarding the relationship between worker demographic (e.g., gender, job tenure, and marital status), substance use, and workplace policies and the actual and potential use of the company EAP. Unlike in most of the existing literature, the authors did not find that gender, marital status, or job dissatisfaction are statistically relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…We were surprised to find only one empirical study that considered age as a predictor of the likelihood of EAP usage (French et al, 1997). French et al examined EAP usage at six worksites across the United States and found age to be a significant predictor of EAP usage at only one of the six worksites.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We were surprised to find only one empirical study that considered age as a predictor of the likelihood of EAP usage (French et al, 1997). French et al examined EAP usage at six worksites across the United States and found age to be a significant predictor of EAP usage at only one of the six worksites.…”
mentioning
confidence: 99%
“…Women have often been found to be underrepresented in EAP caseloads in which the research focused on EAPs that served predominately alcohol-related problems (Cahill, Volicer, & Neuberger, 1982;Gerstein et al, 1993;Young, Reichman, & Levy, 1987). With some exceptions (e.g., Milne, Blum, & Roman, 1994), however, women are typically overrepresented in broad-brush EAP caseloads (Blum, Martin, & Roman, 1992;French et al, 1997;Harris & Fennell, 1988;Poverny & Dodd, 2000). Because the EAP services provided to the organization under investigation are consistent with broad-brush services, we hypothesized the following:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, workplaces can receive assistance to develop and disseminate policies to address stigma and discrimination, work schedules, processes for employee involvement, procedures for recruitment to support inclusion, processes to identify and manage structural sources of stress, wellness initiatives, procedures to guarantee employee confidentiality, and training and practice requirements for supervisors and managers. 54,55 Interventions can also be directed to the objective evaluation and design of jobs and job descriptions. Ideally, this is done with particular attention to both the essential and peripheral demands of jobs to facilitate the development of job accommodations and job characteristics associated with psychological and emotional well-being and productivity.…”
Section: Employer-level Interventionsmentioning
confidence: 99%
“…In order to solve work-related mental health problems, timely communication between EAP and companies is essential. Communication between EAP and companies should be improved, as indicated in previous study 4,6,14) .…”
mentioning
confidence: 99%